Bioelectrical impedance spectroscopy can assist to identify the parathyroid gland during thyroid surgery - Wang, Bin; Liu, Zaoyang; Wu, Jian; Liu, Ying; Wang, Pin; Liu, Hong; Wang, Haobin; Wang, Tielin; Wang, Juan; Tang, Yan; Zhang, Junyan (Frontiers in Endocrinology, 2022)
Objective: This study aimed to explore the effectiveness of bioelectrical impedance spectroscopy in the identification of parathyroid glands during thyroid surgeries. Method: All patients who received thyroid surgeries at our department from January 2018 to February 2020 were recruited for this study. The bioelectrical impedance spectroscopy analyzer was applied to analyze on following tissues: thyroid tissues, lymph nodes, adipose tissues, and the tissues suspected to be parathyroid glands. Postoperative pathological reports were obtained as the golden standard to compare with the characteristic parameters obtained from bioelectrical impedance spectroscopy. The receiver operating characteristic curve analysis was used to assess the diagnostic value and the selection of the optimal threshold of these parameters from bioelectrical impedance spectroscopy. Results: A total of 512 patients were enrolled in the study and 1898 specimens were measured by the bioelectrical impedance spectroscopy analyzer. There were significant differences in the parameter of fc among parathyroid glands, thyroid tissues, lymph nodes, and adipose tissues (252.2±45.8 vs 144.7±26.1, 491.7±87.4, 602.3±57.3; P＜0.001, P＜0.001, P＜0.001). The area under the receiver operating characteristic curves was 0.993 (95%CI: 0.989-0.996) for fc. When the diagnostic criterion of fc was set at 188.85 kHz~342.55 kHz, the sensitivity and specificity to identify parathyroid glands from lymph nodes and adipose tissues were both 100%. At this fc, the sensitivity and specificity to identify parathyroid glands from thyroid tissues were 91.1% and 99.0%, respectively. Conclusion: In conclusion, bioelectrical impedance spectroscopy could assist to differentiate parathyroid glands from peripheral tissues during thyroid surgeries.